Process modeling and analysis of palm oil mill effluent treatment in an up-flow anaerobic sludge fixed film bioreactor using response surface methodology (RSM) - Zinatizadeh, A.A.L.; Mohamed, A.R.; Abdullah, A.Z.; Mashitah, M.D.; Isa, M.H.; Najafpour, G.D. (2006)
In this study, the interactive effects of feed flow rate (QF) and up-flow velocity (Vup) on the performance of an up-flow anaerobic sludge fixed film (UASFF) reactor treating palm oil mill effluent (POME) were investigated. Long-term performance of the UASFF reactor was first examined with raw POME at a hydraulic loading rate (HRT) of 3 d and an influent COD concentration of 44 300 mg/l. Extreme reactor instability was observed after 25 d. Raw POME was then chemically pretreated and used as feed. Anaerobic digestion of pretreated POME was modeled and analyzed with two operating variables, i.e. feed flow rate and up-flow velocity. Experiments were conducted based on a central composite face-centered design (CCFD) and analyzed using response surface methodology (RSM). The region of exploration for digestion of the pretreated POME was taken as the area enclosed by the feed flow rate (1.01, 7.63 l/d) and up-flow velocity (0.2, 3 m/h) boundaries. Twelve dependent parameters were either directly measured or calculated as response. These parameters were total COD (TCOD) removal, soluble COD (SCOD) removal, effluent pH, effluent total volatile fatty acid (TVFA), effluent bicarbonate alkalinity (BA), effluent total suspended solids (TSS), CH4 percentage in biogas, methane yield (YM), specific methanogenic activity (SMA), food-tosludge ratio (F/M), sludge height in the UASB portion and solid retention time (SRT). The optimum conditions for POME treatment were found to be 2.45 l/d and 0.75 m/h for QF and Vup, respectively (corresponding to HRT of 1.5 d and recycle ratio of 23.4:1). The present study provides valuable information about interrelations of quality and process parameters at different values of the operating variables.